Repetitive Mild but Not Single Moderate Brain Trauma Is Associated with TAR DNA-Binding Protein 43 Mislocalization and Glial Activation in the Mouse Spinal Cord - Tamara Janković; Jelena Rajič Bumber; Nika Gržeta Krpan; Petra Dolenec; Marc Jaeger; Jasna Kriz; Gordana Župan; Kristina Pilipović (Biomedicines)
Background/Objectives: Traumatic brain injury (TBI) occurs after a sudden mechanical force to the skull and represents a significant public health problem. Initial brain trauma triggers secondary pathophysiological processes that induce structural and functional impairment of the central nervous system, even in the regions distant to the lesion site. Later in life, these changes can be manifested as neurodegenerative sequalae that commonly involve proteinopathies, such as transactive DNA-binding protein 43 (TDP-43). The progression of pathophysiological changes to the spinal cord motor neurons has been detected after repetitive TBI, while such changes have been less investigated after single TBI. Methods: Single TBI was applied over the left parietal cortex of mice by using the lateral fluid percussion injury apparatus and a separate cohort of animals received repetitive mild TBI by weight drop apparatus, with two mild injuries daily, for five days in a row. Mice were sacrificed after single moderate or last mild TBI and their spinal cords were prepared for the analyses. For both types of injury, sham-injured mice were used as a control group. Results: Here, we found an early formation of toxic phosphorylated TDP-43 species on the 3rdday post-injury which, together with TDP-43 cytoplasmic translocation, remained present in the subacute period of 14 days after repetitive mild but not single moderate TBI. During the subacute period following a repetitive brain trauma, we found an increased choline acetyltransferase protein expression and significant microgliosis in the cervical part of the spinal cord, which was not detected after single TBI. Astrogliosis presented similarly after both experimental procedures. Conclusions: This study demonstrates the differences in the spinal cord TDP-43 pathology and inflammation, depending on the brain trauma type, and may contribute to the development of targeted therapeutic strategies.